Generic keys for the identification of larval Dytiscidae from Argentina (Coleoptera: Adephaga) - Mariano C MICHAT (Revista de la Sociedad Entomológica Argentina, 2008)
Generic keys for the identification of larvae of Dytiscidae from Argentina are presented. A total of 27 dytiscid genera are recognized in Argentina, included in 16 tribes and seven subfamilies. Twenty-two of the 27 genera are included in the keys. The remaining five genera could not be included because their larvae are unknown (Bidessonotus Régimbart, Brachyvatus Zimmermann, Hemibidessus Zimmermann, Neobidessus Young) or remain poorly known (Cybister Curtis). The keys are presented in English and Spanish. Morphological as well as chaetotaxic characters were included, and an emphasis was made to include easily seen and identifiable characters. However, due to the small size of many dytiscid larvae, some of the characters mentioned in the keys (especially the chaetotaxic ones) are difficult to visualize through the observation with a stereoscopic microscope. Therefore, the use of a compound microscope for the identification is recommended.